2019
DOI: 10.1007/s00709-019-01363-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of plastids and mitochondria during male gametophyte formation in Tinantia erecta (Jacq.) Fenzl

Abstract: During meiosis in microsporogenesis, autonomous cellular organelles, i.e., plastids and mitochondria, move and separate into daughter cells according to a specific pattern. This process called chondriokinesis is characteristic for a given plant species. The key criterion for classification of the chondriokinesis types was the arrangement of cell organelles during two meiosis phases: metaphase I and telophase I. The autonomous organelles participate in cytoplasmic inheritance; therefore, their precise distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Moreover, an unusually strong perinuclear radial microtubule system occurring in telophase I and II in the species studied and the presence of a phragmoplast in a small space devoid of cell organelles between aggregates composed of cell organelles surrounding the progeny nuclei were observed. It was found that meiosis in L. thuringiaca microsporogenesis is similar to that occurring in most plants with simultaneous cytokinesis, but the movement of organelles during meiosis is very unique and specific (Brownfield et al, 2015;Marciniec et al, 2019). Microtubules were found to be closely associated with karyokinesis and chondriokinesis during microsporogenesis in L. thuringiaca, and thus determined the formation of functional pollen grains (Tchórzewska et al, 2008).…”
Section: Phytochemical Constituents Class Activities Referencesmentioning
confidence: 96%
“…Moreover, an unusually strong perinuclear radial microtubule system occurring in telophase I and II in the species studied and the presence of a phragmoplast in a small space devoid of cell organelles between aggregates composed of cell organelles surrounding the progeny nuclei were observed. It was found that meiosis in L. thuringiaca microsporogenesis is similar to that occurring in most plants with simultaneous cytokinesis, but the movement of organelles during meiosis is very unique and specific (Brownfield et al, 2015;Marciniec et al, 2019). Microtubules were found to be closely associated with karyokinesis and chondriokinesis during microsporogenesis in L. thuringiaca, and thus determined the formation of functional pollen grains (Tchórzewska et al, 2008).…”
Section: Phytochemical Constituents Class Activities Referencesmentioning
confidence: 96%
“…However, there are not many reports of similar polar organelle grouping in plants that exhibit a successive-type of cytokinesis. A notable example of this is reported in the monocot widow’s tears ( Tinantia erecta ), in which plastids and mitochondria were observed to group at the cell poles during early prophase I ( Marciniec, Zieba et al, 2019 ).…”
Section: Temporal Dynamics and Localisation Of Different Types Of Org...mentioning
confidence: 96%
“…Tinantia erecta is a native species of Latin America that belongs to the Commelinaceae family and that can be found as a wild plant mainly in crop fields of corn, coffee, and beans. It is used as forage, as an edible wild plant, and as an ornament (Villaseñor and Espinosa, 1998;Mera-Ovando et al, 2003;Marciniec et al, 2019). Due to its high adaptability and distribution, this species could serve as a source of compounds with potential antifungal activity.…”
Section: Introductionmentioning
confidence: 99%